2023
DOI: 10.1002/anie.202301937
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Stimuli Responsive Luminescence and Domino Phase Transition of Hybrid Copper Halides with Nonlinear Optical Switching Behavior

Abstract: Although phase transition materials (PTMs) under external stimuli are of great research interest duo to their rich potential applications, it is still challenging to explore multi-responsive PTMs. Herein, two different phases of organic-inorganic hybrid copper-based halides, α-and β-Gua 3 Cu 2 I 5 (Gua + = CN 3 H 6 + ), were synthesized by solvent evaporation method, which they crystalize in the noncentrosymmetric space group Fdd2 with zero-dimensional structure and centrosymmetric space group C2/c with one-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 46 publications
(2 reference statements)
1
36
0
Order By: Relevance
“…[11][12][13][14][15] Notably, the compounds containing p-conjugated organic moieties have attracted the most attention, and many promising NLO materials in such classes have been reported, such as KLi(HC 3 N 3 O 3 )$2H 2 O (5.3 × KDP), 11 Lu 5 (C 3 N 3 O 3 )(OH) 12 (4.2 × KDP), 12 C(NH 2 ) 3 SO 3 F (5 × KDP), 13 (C 5 H 6 ON) + (H 2 PO 4 ) − (3 × KDP), 14 and [o-C 5 H 4 NHOH] 2 [-I 7 O 18 (OH)]$3H 2 O (8.5 × KDP). 15 Alongside these compounds, several organic-inorganic metal halides (OIMHs) formed from the combination of a p-conjugated organic cation with a metalhalide polyhedron have also been discovered to show NLO performance, such as (H 7 C 3 N 6 )(H 6 C 3 N 6 )MCl 3 (M = Hg and Zn; 5 × and 2.8 × KDP), 16,17 [C 18 H 21 N 4 ][AgX 3 ]X (X = Cl, Br, and I, 6.2, 6.5 and 7.6 × KDP), 18 a-(CN 3 H 6 ) 3 Cu 2 I 5 (1.8 × KDP), 19 and (C 6 H 11 N 2 )PbBr 3 (8 × KDP). 20 It is also worth studying the NLO properties of non-pconjugated OIMHs, which is similar to the approach of expanding the chemical system from p-conjugated borates to non-p-conjugated phosphates or sulfates.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Notably, the compounds containing p-conjugated organic moieties have attracted the most attention, and many promising NLO materials in such classes have been reported, such as KLi(HC 3 N 3 O 3 )$2H 2 O (5.3 × KDP), 11 Lu 5 (C 3 N 3 O 3 )(OH) 12 (4.2 × KDP), 12 C(NH 2 ) 3 SO 3 F (5 × KDP), 13 (C 5 H 6 ON) + (H 2 PO 4 ) − (3 × KDP), 14 and [o-C 5 H 4 NHOH] 2 [-I 7 O 18 (OH)]$3H 2 O (8.5 × KDP). 15 Alongside these compounds, several organic-inorganic metal halides (OIMHs) formed from the combination of a p-conjugated organic cation with a metalhalide polyhedron have also been discovered to show NLO performance, such as (H 7 C 3 N 6 )(H 6 C 3 N 6 )MCl 3 (M = Hg and Zn; 5 × and 2.8 × KDP), 16,17 [C 18 H 21 N 4 ][AgX 3 ]X (X = Cl, Br, and I, 6.2, 6.5 and 7.6 × KDP), 18 a-(CN 3 H 6 ) 3 Cu 2 I 5 (1.8 × KDP), 19 and (C 6 H 11 N 2 )PbBr 3 (8 × KDP). 20 It is also worth studying the NLO properties of non-pconjugated OIMHs, which is similar to the approach of expanding the chemical system from p-conjugated borates to non-p-conjugated phosphates or sulfates.…”
Section: Introductionmentioning
confidence: 99%
“…In these hybrid copper halides, the inorganic units of the 0D structure can be categorized into CuX 2 , Cu 2 X 4 , Cu 2 X 5 , Cu 4 X 6 , and so on (X = Cl, Br, I). 16,18,20,24 Although the synthesis of the transition metal-based binuclear and polynuclear compounds has been previously reported, there is a lack of research on synthesizing hybrid copper with different inorganic units using the same organic cations. [25][26][27][28] Previous research has demonstrated that the influence of inorganic units on the optical properties of hybrid halides is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…), a great number of hybrid metal halides have been explored as promising materials for various NLO applications owing to their fascinating advantages of inorganic metal frameworks and organic molecules. [17][18][19][20][21][22] Inspired by the classic three-dimensional (3D) metal halide perovskite prototype AMX 3 (A = organic cations, M = bivalent metal cation, and X = halogen anion), bivalent metal cations are replaced by heterovalent metal ions to form perovskite-like derivatives and MX n (n = 2, 3, 4, 5) units with different coordination numbers. Among the perovskite-like derivatives, a linear structure [MX 2 ] unit is very rarely discovered, though they have demonstrated inherent advantages to achieve large SHG effects and birefringence attributed to their relatively large polarities and the ordered arrangement of linear anionic groups.…”
Section: Introductionmentioning
confidence: 99%